PENGARUH MODEL PEMBELAJARAN OPEN ENDED BERBASIS PENILAIAN PROYEK TERHADAP KOMPETENSI PENGETAHUAN PPKn SISWA - Wiyasa, IKN (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2018)
The purpose of this research was to know the significant difference of knowledge competence of PPKn group of students which were taught by Open Ended learning model based on project assessment with group of students taught by conventional learning in fourth grades of SD Gugus I Gianyar Sub District Academic Year 2017/2018. This research was a quasi-experimental study with non-equivalent group design. Population in this research were all fourth graders of SD Gugus I Gianyar Sub District Academic Year 2017/2018 which amounted to 343 people. Determination of the sample in this reseach used random sampling technique with existing class scramble, then to determin of both of experimental and control groups were drawed so the fourth grade Melati SD Negeri 2 Gianyar as 36 students as experimental class and fourth grade A SD Negeri 1 Gianyar as much 44 students as a control class group. The student's knowledge competence data were collected with an ordinary double-choice objective test instrument of 30 validated questions. The gain score normalization value of fourth grades Melati under the average of 15 people and which reached an average of 21 people while the gain score normalization value of fourth grades A which were below the average of 21 people and who reached an average of 23 people. The result of t-test analysis shows tcalculate = 2,494> ttable (ɑ = 0,05, dk = 78) = 1,991 so H0 was rejected and Ha accepted. In accordance with these results can be concluded Open Ended learning model based on project assessment affect the competence of knowledge PPKn fourth graders of SD Gugus I Gianyar Sub District Academic Year 2017/2018. For researchers who have similarities of variables, the results of this research can be used as a relevant research. Keywords: open ended, project assessment, PPKn